Non-Linguistic Approach in The Formation of The Arabic Language Environment - Aulia Rahman (INAIFAS PRESS, 2023)
This research tries to explore non-linguistic factors as an approach in the formation of the Arabic language environment. Meanwhile, related to the research background above, researchers tried to analyze the role and non-lingustic approach in Ma’had Abu Ubaidah Medan. This research is an analytical description research sourced from literature surveys and experience surveys. The thing found in this study is that the non-linguistic approach in the formation of the Arabic language environment in Ma’had Abu Ubaidah Medan has several aspects and each aspect causes implications for the development of students’ Arabic language skills. Attention to non-linguistic approaches results in a positive in the formation of the Arabic language environment.